Usability Studies for Power Users: applied for email desktop client - Bárbara de Jesus Correia (2015)
Usability engineering field is related with human computer interaction (HCI), with at least 30 years, which has gained prominence in the technological world and currently it is the subject of several studies. Users give more value to their user experience so the market has to take into account their preferences.A system with low usability will be a hindrance to the user making the user experience negative. This problem reduces the user productivity and his satisfaction.Currently email applications have much use, however they present some usability problems which are meant to be solved with this dissertation. The main goals of this dissertation are the user experience study measuring the efficiency of use and the application improvement in order to please the expert users' needs. The application in study enables the visualization of the email messages as well as any operation inherent to ordinary email clients. In addition, the application has some innovative features which will have special attention during the study.In this case study it will be applied four main usability engineering methods. Initially, the selected users will be observed directly in their natural environment. Then, a survey will be delivered to get background information from users about their experience with the email. The next step is to perform card sorting and heuristic evaluation to evaluate the interface architecture and navigation. The following method is usability testing, selecting representative users to execute some tasks on the interface.After the completion of each method the data will be analysed according to usability parameters. This is an iterative process since if the main goals are not met in the first round, then new tests will be made until an acceptable solution is found.In short, it is intended to release a product which satisfies the power users needs so that they have a high quality user experience.